2013
DOI: 10.1093/nar/gkt1270
|View full text |Cite
|
Sign up to set email alerts
|

Expression Atlas update—a database of gene and transcript expression from microarray- and sequencing-based functional genomics experiments

Abstract: Expression Atlas (http://www.ebi.ac.uk/gxa) is a value-added database providing information about gene, protein and splice variant expression in different cell types, organism parts, developmental stages, diseases and other biological and experimental conditions. The database consists of selected high-quality microarray and RNA-sequencing experiments from ArrayExpress that have been manually curated, annotated with Experimental Factor Ontology terms and processed using standardized microarray and RNA-sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
266
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(267 citation statements)
references
References 6 publications
0
266
0
1
Order By: Relevance
“…In total, these three segments harbour 58 transcripts of which 39 are expressed in skin 11 . TGFB2 is the closest gene to the association signal at 1q41, located 226 kb from the lead SNP rs1159268.…”
Section: Resultsmentioning
confidence: 99%
“…In total, these three segments harbour 58 transcripts of which 39 are expressed in skin 11 . TGFB2 is the closest gene to the association signal at 1q41, located 226 kb from the lead SNP rs1159268.…”
Section: Resultsmentioning
confidence: 99%
“…2). Although NGF mRNA was clearly expressed in human, an examination of the Expression Atlas database (Petryszak et al, 2013) revealed no indication of TRKA mRNA expression in human and bovine adipose tissue. A possible explanation would be that the TrkA protein enters the adipose cells through the signaling endosomes produced by peripheral axons of neurons.…”
mentioning
confidence: 97%
“…The integration of all these different data and annotations in a searchable database requires new bioinformatics instruments and ontologies, which also enable direct interaction with existing resources holding, for example, annotated gene expression data [18,19].…”
Section: Discussionmentioning
confidence: 99%